The Use of ICT among University’s Lecturers in Medan, Indonesia: A Comparative Study - Andre Hasudungan Lubis; Syed Zulkarnain Syed Idrus; Asiah Sarji, (Journal of Human Development and Communication (JoHDeC), 2025)
This study is to discover the difference use of ICT between faculty members in Medan, Indonesia with regards to their demographic factors namely: gender, age, teaching experiences, educational level, and department of origin. A total of 260 samples were taken from the overall populations, where a survey was conducted among the academicians from three largest private universities. After the cross-tabulation statistical analysis was completed, the findings are promising. The gender, age and department of origin of university’s lecturers are proven to have a significance on ICT usage. In contrast, after many years of teaching experiences and with their educational level, it is found that it did not have any influence towards the utilization of the technology in their learning process. Thus, there are similar patterns of usage that were also found among them.